Modelo MRP en empresas de servicio (2018)
Through the material requirements planning (MRP) model, with the main objective of offering a more practical, precise and disciplined approach to determining the material requirements of the company, it is intended to develop a dependent demand model, thanks to the help of a computer tool, so it is decided to use Microsoft Access 2013, creating a database that better supports the planning in service companies. Therefore, an investigation is made on the different problems that are present in this sector, and through the MRP models taken as an example, these adequate solutions were observed that allowed to help a better control of the different involved elements of bad planning, being able to fulfill in organizations or manufacturing companies meet the needs strategically proposed in the medium term, both those requirements both the customer and the interests of organizations. This is how this MRP model for service companies can facilitate planning processes, with the creation of an MRP model for this sector with the main elements of dependent demand planning, achieving greater efficiency in the delivery activities of service